Dynamic Geometry: P97

Geometry Level 4

The diagram shows two black circles with radius 1 1 . Their centers (purple points) move appart horizontaly. The cyan rectangle is inscribed in the overlapping space between the two circles. It is always the rectangle which area is maximum . The blue point traces a locus (red curve). If the green point is the origin is a coordinate system, the equation of the locus can be written as:

y = x p + x 2 x 2 q y=\sqrt{\dfrac{x\sqrt{p+x^2}-x^2}{q}}

where p p and q q are positive integers. Find p + q p+q .


The answer is 6.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

1 solution

Chew-Seong Cheong
Mar 24, 2021

Let an arbitrary point on the locus be P ( x , y ) P(x,y) and the distance of the center either circle to the origin ( 0 , 0 ) (0,0) of the x y xy -plane be a a . By Pythagorean theorem ,

( x + a ) 2 + y 2 = 1 2 y = 1 ( x + a ) 2 (x+a)^2 + y^2 = 1^2 \implies y = \sqrt{1-(x+a)^2}

And the area of the rectangle is A = 4 x y = 4 x 1 ( x + a ) 2 A=4xy=4x\sqrt{1-(x+a)^2} . To find the relation between x x and y y , when A A is maximum,

d A d x = 4 1 ( x + a ) 2 4 x ( x + a ) 1 ( x + a ) 2 Putting d A d x = 0 1 ( x + a ) 2 = x ( x + a ) 1 ( x + a ) 2 1 ( x + a ) 2 = x ( x + a ) or y 2 = x ( x + a ) ( x + a ) 2 + x ( x + a ) 1 = 0 a 2 + 3 a x + 2 x 2 1 = 0 Solving the quadratic for a a = x 2 + 4 3 x 2 Since a > 0 \begin{aligned} \frac {dA}{dx} & = 4 \sqrt{1-(x+a)^2} - \frac {4x(x+a)}{\sqrt{1-(x+a)^2}} & \small \blue{\text{Putting }\frac {dA}{dx}=0} \\ \sqrt{1-(x+a)^2} & = \frac {x(x+a)}{\sqrt{1-(x+a)^2}} \\ 1 - (x+a)^2 & = x(x+a) & \small \blue{\text{or } y^2 = x(x+a)} \\ (x+a)^2 + x(x+a) - 1 & = 0 \\ a^2 + 3ax + 2x^2 - 1 & = 0 & \small \blue{\text{Solving the quadratic for }a} \\ \implies a & = \frac {\sqrt{x^2+4}-3x}2 & \small \blue{\text{Since }a > 0} \end{aligned}

Since y 2 = x ( x + a ) = x 2 + x x 2 + 4 3 x 2 = x 2 + 4 x 2 2 y^2 = x(x+a) = x^2 + x \cdot \dfrac {\sqrt{x^2+4}-3x}2 = \dfrac {\sqrt{x^2+4}-x^2}2 ,

y = x 2 + 4 x 2 2 \implies y = \sqrt{\frac {\sqrt{x^2+4}-x^2}2}

Therefore p + q = 4 + 2 = 6 p+q = 4+2 = \boxed 6 .

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...